2021
DOI: 10.1101/2021.09.14.21263446
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Time-dependent prediction of mortality and cytomegalovirus reactivation after allogeneic hematopoietic cell transplantation using machine learning

Abstract: Allogeneic hematopoietic cell transplantation (HCT) treats high-risk hematologic diseases effectively but can entail HCT-specific complications, which may be minimized by appropriate patient management and accurate, individual risk estimation. Existing clinical scores typically provide a single risk assessment before HCT and do not incorporate additional data as it becomes available. We developed machine learning models which integrate both baseline patient data and time-dependent laboratory measurements to in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…In some of them the AUC reaches acceptable for practical application levels: in the study Pan L. et al the developed model demonstrated high AUC level of 0.904 [34]. Interestingly, the number of studies based on posttransplant variables is even more limited: in one of them by Eisenberg L. et al machine models provided wellcalibrated, time-dependent risk predictions and achieved appropriate level of AUC of 0.92 and 0.83 for prediction of mortality and CMV reactivation, respectively, in a 21-day time window after allo-HSCT [35]. However, to the best of our knowledge, there are no reliable machine learning approaches to predict relapse in adult Ph-positive ALL patients after allo-HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…In some of them the AUC reaches acceptable for practical application levels: in the study Pan L. et al the developed model demonstrated high AUC level of 0.904 [34]. Interestingly, the number of studies based on posttransplant variables is even more limited: in one of them by Eisenberg L. et al machine models provided wellcalibrated, time-dependent risk predictions and achieved appropriate level of AUC of 0.92 and 0.83 for prediction of mortality and CMV reactivation, respectively, in a 21-day time window after allo-HSCT [35]. However, to the best of our knowledge, there are no reliable machine learning approaches to predict relapse in adult Ph-positive ALL patients after allo-HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…In some of them, the AUC reaches acceptable for practical application levels: in the study by Pan et al, the model demonstrated a high AUC level of 0.904 34 . Interestingly, the number of studies based on posttransplant variables is even more limited: in one of them by Eisenberg et al, machine models provided well-calibrated, time-dependent risk predictions and achieved appropriate levels of AUC of 0.92 and 0.83 for prediction of mortality and CMV reactivation, respectively, in a 21-day time window after allo-HSCT 35 . However, to our knowledge, there are no reliable machine-learning approaches to predict relapse in adult Ph-positive ALL patients after allo-HSCT.…”
Section: Discussionmentioning
confidence: 99%